AKIBAT HUKUM PEMBERHENTIAN TIDAK DENGAN HORMAT DARI DINAS ANGGOTA KEPOLISIAN MENURUT UU No. 2 TAHUN 2002 TENTANG KEPOLISIAN NEGARA REPUBLIK INDONESIA (STUDI KASUS NO. PUT. KEPP./02/VIII/2020/KKEP): Legal Consequences Of Dishonormal Dismissal From The Police Service (Study of. KEPP./02/VIII/ 2020/ KKEP) - Renaldhy Ildha Subagja; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2024)
Dishonorable Dismissal of Brigadier Iis Sudarsono according to No. Put. KEPP/02/VIII/2020/KKEP. Discrepancies were found in the formal juridical process of PTDH law enforcement as regulated in Perkap No. 19 of 2012 and Perkap no. 14 of 2011 concerning the Police Professional Code of Ethics, which should be strict and rigid. The legal issues in this research are; Is the Code of Ethics Commission's decision in Decision No. PUT. KEPP./02/VIII/2020/KKEP in accordance with Law no. 2 of 2002 concerning the National Police of the Republic of Indonesia, and what are the legal consequences of this decision according to Law no. 2 of 2002? Normative research method with secondary data. The research results and conclusions are that the decision is not in accordance with Law no. 2 of 2002, so it was declared null and void and invalid. The legal consequence is decision no. Put. KEPP/02/VIII/2020/KKEP is considered null and void and has legal consequences for the decisions that will be taken in this Professional Code of Ethics hearing.